Putative Role of the Aldo-Keto Reductase from Trypanosoma cruzi in Benznidazole Metabolism - Garavaglia, Patricia A (2016)
Fil: Garavaglia, Patricia Andrea. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.